2020
DOI: 10.3390/molecules25194511
|View full text |Cite
|
Sign up to set email alerts
|

Two New Indole Alkaloids from Toad Venom of Bufo bufo gargarizans

Abstract: Two new indole alkaloids, Bufotenidine B (2) and Bufocarboline A (6), along with seven known indole alkaloids (1, 3–5, and 7–9) and three organic acids (10–12), were isolated from the water extract of toad venom. The structures of the new alkaloids were elucidated by extensive spectroscopic methods. The absolute configurations of 4, 6, and 8 were determined for the first time by electronic circular dichroism (ECD) calculations. The cytotoxic activity of all compounds was tested against human malignant melanoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…While bufalin effectively induces cell cycle arrest, it shows different patterns in different cell types. Bufalin could induce cell cycle arrest at the S phase in pancreatic cancer BxPC3-luc2 cells ( Liu et al, 2016 ), lung cancer A549 cells ( Zhang and Fu, 2017 ) at G2/M phase in GBM U251 and U87MG cells ( Zhang et al, 2017 ), TNBC MDA-MB-231 and HCC-1937 cells ( Chen et al, 2020b ), pancreatic cancer PANC-1, and CFPAC-1 cells ( Li et al, 2014 ), cervical cancer Siha cells ( Liu et al, 2016 ). These results suggested that bufalin may interfere with cancer cell division, which can be further utilized with certain anticancer therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While bufalin effectively induces cell cycle arrest, it shows different patterns in different cell types. Bufalin could induce cell cycle arrest at the S phase in pancreatic cancer BxPC3-luc2 cells ( Liu et al, 2016 ), lung cancer A549 cells ( Zhang and Fu, 2017 ) at G2/M phase in GBM U251 and U87MG cells ( Zhang et al, 2017 ), TNBC MDA-MB-231 and HCC-1937 cells ( Chen et al, 2020b ), pancreatic cancer PANC-1, and CFPAC-1 cells ( Li et al, 2014 ), cervical cancer Siha cells ( Liu et al, 2016 ). These results suggested that bufalin may interfere with cancer cell division, which can be further utilized with certain anticancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“… Chen et al (2020b) found that bufalin suppressed the proliferation (0.5 μM), colony formation (0.5 and 1 μM) of TNBC MDA-MB-231 and HCC-1937 cell lines, arresting cells at G2/M phase ( Chen et al, 2020b ), same as in GBM cells ( Zhang et al, 2017 ). Bufalin (0.5 µM, 48 h) caused apoptosis of both cell lines at ∼10%.…”
Section: Introductionmentioning
confidence: 99%
“…Both alkaloids and bufadienolides are among the most prominent and most-studied compounds in toad venom. Growing studies have confirmed that both alkaloids and bufadienolides can work in treating cardiovascular diseases and cancers ( Chen et al, 2020 ). Our special and major interest in this review falls in these bufadienolides ( Figure 2 ).…”
Section: Bufadienolides In Toad Venom and Their Therapeutic Implicati...mentioning
confidence: 99%
“…Of note, the cinobufacini injection, as a sanctioned therapy, has been used in the management of cancer, including lung and liver malignancies, in China [4,5]. Research has elucidated that the pharmacologically active components within toad venom chiefly comprise alkaloids and bufadienolides, which are distinguished for their diverse bioactive activity for different diseases [6][7][8][9]. Previous studies have shown that bufadienolides demonstrate potent cytotoxic activities against diverse cancer cell lines in vitro and in vivo, with IC 50 values in the nanomolar range [10].…”
Section: Introductionmentioning
confidence: 99%